2022
DOI: 10.3390/economies10080189
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Sustainable Growth of SMEs in Developing Countries: The Case of Ethiopia

Abstract: Small and medium-sized businesses (SMEs) played a significant role in domestic employment and inclusive GDP in developing countries such as Ethiopia. Accordingly, the purpose of this study is to investigate the determinants of sustainable growth of SMEs in developing countries, notably in Ethiopia. To achieve the objectives of this study, both descriptive and explanatory research designs were used. In addition to this, primary data was collected from SMEs engaged in service, manufacturing, trade, construction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The expansion and viability of MSMEs are favorably impacted by the availability of advanced transportation networks, utilities, and technological infrastructure (Hossain & Pathak, 2023;Prasetyo & Ellitan, 2023). The literature that is currently available emphasizes the critical role that infrastructure plays in fostering an environment that is favorable for MSMEs to operate in (Abdissa et al, 2022). Studies have demonstrated that MSMEs' ability to grow and survive might be hampered by things like inadequate infrastructure (Bayineni & Chagal, 2022).…”
Section: Discussion a Infrastructure And Msme Performancementioning
confidence: 99%
“…The expansion and viability of MSMEs are favorably impacted by the availability of advanced transportation networks, utilities, and technological infrastructure (Hossain & Pathak, 2023;Prasetyo & Ellitan, 2023). The literature that is currently available emphasizes the critical role that infrastructure plays in fostering an environment that is favorable for MSMEs to operate in (Abdissa et al, 2022). Studies have demonstrated that MSMEs' ability to grow and survive might be hampered by things like inadequate infrastructure (Bayineni & Chagal, 2022).…”
Section: Discussion a Infrastructure And Msme Performancementioning
confidence: 99%
“…The long-term sustainability of Ethiopian SMEs is substantially hindered by political instability, corruption, and COVID-19 (Abdissa et al, 2022). Ethiopian political uncertainty has a negative and considerable influence on the survival of SMEs (Abdissa et al, 2022). Access to finance remains the leading barrier to the development of MSEs in Ethiopia due to the existence of inadequate loan size, borrowing cost and collateral requirement.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The long-term sustainability of Ethiopian SMEs is substantially hindered by political instability, corruption, and COVID-19 (Abdissa et al, 2022). Ethiopian political uncertainty has a negative and considerable influence on the survival of SMEs (Abdissa et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable development is a term that was initially cited in the report on the restrictions on growth that was presented in 1972 (Abdissa et al, 2022). After this, it was mentioned in the Brundtland Report in…”
Section: Introductionmentioning
confidence: 99%